The risks associated with the logistics chain of scientific research from the choice of research area to the analysis of obtained results - Litvinova, T. M.; U. Glazkova, I. U.; Kazieva, L.Sh. Kazieva Sh.; Kurinnaya, A. C.; Dezhurko-Korol, V. A. (Opción, 2019)
This article looks at the most common risks associated with the logistics chain of scientific research aiming to visualize, optimize and simplify the process of conducting scientific activity. With the help of systematic research methodology and information analysis, the authors have developed and suggested a logistics chain of scientific research with due account for risks that can arise at different stages of scientific research. The process of acquiring knowledge presented as a logistics chain of scientific research with consideration of risks is a set of certain actions aimed at achieving the set goals and getting reliable results.